Orchiectomy and Radiotherapy for Stage I–II Testicular Seminoma: A Prospective Evaluation of Short-Term Effects on Body Image and Sexual Function. (1st January 2015) - Wortel, Ruud C.; Alemayehu, Wendim Ghidey; Incrocci, Luca
ABSTRACT: Introduction: Orchiectomy followed by infradiaphragmatic radiotherapy is a common treatment for stage I–II testicular seminoma. Long-term effects of orchiectomy and radiotherapy for testicular seminomas on body image and sexual function have been reported; however, few data are available on short-term effects. Patients are usually of reproductive age and sexually active; therefore, short-term effects on body image and sexual function should also be studied. Aims: To prospectively evaluate short-term effects of orchiectomy and radiotherapy on body image and sexual function in testicular seminoma patients. Methods: Questionnaires on body image and sexual function were prospectively distributed to all testicular seminoma patients treated between 1999 and 2013. The questionnaire distributed prior to radiotherapy was returned by 161 patients; 133 (82%) returned the second after 3 months, and 120 (75%) completed the questionnaire after 6 months. Main Outcome Measures: Body image and sexual function as assessed by a Dutch questionnaire on body image and sexuality after radiotherapy and orchiectomy. Results: Median age was 36 years (range 18–70). After orchiectomy, 48% expressed fertility concerns, and 61% reported their body had changed. Six months after treatment, erectile rigidity was significantly decreased compared with prior to radiotherapy ( P = 0.016), and 23% reported decreased sexual interest, activity, and pleasure. Changes in body image were significantly associated with decreased sexual interest, pleasure, and erectile function. Even though 45% reported that treatment negatively affected their sexual life, the number of sexually active patients remained stable at 91%. [Correction added on 12 November 2014, after first online publication: 'prior radiotherapy' was corrected to 'prior to radiotherapy'.] Conclusions: Short-term effects of treatment included fertility concerns and changes in body image. Reported erectile rigidity was significantly decreased after 6 months, as were sexual interest, activity, and pleasure. Disease and treatment had negative effects on sexual life, and changes in body image were associated with sexual dysfunction. Therefore, body image and sexual functioning should be addressed at an early stage in order to offer adequate treatment and counseling.